Математична модель нестаціонарних режимів по лінійній ділянці газогону з урахуванням кінетичної енергії - Фесенко, К. П. (ХНУРЕ, 2024)
In this work, the non-stationary non-isothermal mode of gas transport along the linear section of the gas pipeline, which consists of two consecutive pipeline sections of different diameters, is considered. The need to model a given structure may arise as a result of an unexpected situation in which the analysis of changes in the process of gas transportation through sections of different diameters is required.
Keywords: математична модель нестаціонарних режимів течії газу; лінійна ділянка газогону